Integer arithmetic with delayaed carry - Охрименко, Андрей Александрович (Ukrainian Information Security Research Journal, 2014)
Cryptographic transformation with public key are widelyused in directional encryption, shared secret generationand digital signature. Therefore, performance improvingof cryptographic transformations with public key is actualproblem. Performance improving of operations on integersis a potential solution to this problem. Author proposeDCF representation of integers in which the numberis split into machine words, where each word has informationblock and carry block. Author propose algorithmsof basic arithmetic operations with delayed carry, providesrecommendations for effective software implementationof arithmetic operations (addition, subtraction).